Outer Plexiform Layer Angle: A Prognostic Factor for Idiopathic Macular Pucker Surgery - Ding-Ying Liao; Jorn-Hon Liu; Yu-Ping Zheng; Jian-Ming Wang; Hsiao-Ming Chao (Journal of Ophthalmology)
Purpose. To investigate the efficacy of idiopathic macular pucker (epimacular membrane) surgery and to identify the possible prognostic factor. Methods. This was a retrospective study which enrolled 38 patients with idiopathic macular pucker who underwent 23-gauge pars plana vitrectomy (PPV) with indocyanine green-assisted peeling of epiretinal membrane (ERM) and internal limiting membrane (ILM). Visual outcomes were assessed at the baseline and during the follow-up including best-corrected visual acuity (BCVA) and metamorphopsia score, as well as outer plexiform layer (OPL) angle and central retinal thickness (CRT) using spectral-domain optical coherence tomography (SD-OCT). A comparison was made between patients with the prepeeling CRTs ≥500 μm and those <500 μm. A comparison was also made between patients with the prepeeling OPL angles ≥130° and those <130°. Based on the prepeeling parameters, the correlations between various prepeeling and postpeeling visual functions were analyzed. Results. Mean follow-up was 36.07 ± 4.62 months (range 1.30–96.70 months). BCVA was significantly improved from 0.26 ± 0.03 to 0.67 ± 0.04 p<0.001; metamorphopsia score was significantly reduced from 1.42 ± 0.16 to 0.61 ± 0.08 p<0.001; CRT was significantly decreased from 519.62 ± 13.41 μm to 385.37 ± 8.97 μm p<0.001. Greater prepeeling OPL angle (≥130°) was associated with significantly greater BCVA improvement (Snellen E/LogMAR: p=0.01/0.03) and greater metamorphopsia reduction p=0.03, as compared to smaller OPL angle (<130°) with less BCVA improvement and less metamorphopsia reduction. However, the final BCVA improvement and metamorphopsia reduction relevant to the prepeeling smaller CRT (<500 μm) did not significantly differ from that relevant to the prepeeling greater CRT (≥500 μm; p>0.05). Endophthalmitis, retinal tear, or retinal detachment was not observed after peeling. Conclusion. Indocyanine green-assisted ERM/ILM peeling combined with small gauge vitrectomy is associated with significant visual acuity improvement and metamorphopsia reduction in patients with idiopathic macular pucker. Greater prepeeling OPL angle rather than CRT might act as a useful prognostic factor in predicting better final visual functional outcomes.